1996
DOI: 10.1086/177391
|View full text |Cite
|
Sign up to set email alerts
|

Branching Fractions and Oscillator Strengths for Fe II Transitions from the 3d 6( 5D)4p Subconfiguration

Abstract: New experimental branching fractions and transition probabilities are reported for 56 transitions in Fe II. The branching fractions are measured with a Fourier transform spectrometer and also with a highresolution grating spectrometer on an optically thin hollow cathode discharge. Highly accurate experimental radiative lifetimes from the recent literature provide the normalization required to convert our branching fractions into absolute transition probabilities. Results are compared with experimental and theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 16 publications
(20 reference statements)
5
52
0
1
Order By: Relevance
“…This was done for more than half of the levels giving us a sufficient absolute wavelength calibration for all the laser dyes used. (24) [1] Bergeson et al (1996). * Lifetime taken from Schade et al (1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done for more than half of the levels giving us a sufficient absolute wavelength calibration for all the laser dyes used. (24) [1] Bergeson et al (1996). * Lifetime taken from Schade et al (1988).…”
Section: Resultsmentioning
confidence: 99%
“…The error bars of our data include statistical and estimated systematic uncertainties. (18) [1] Bergeson et al (1996). * Lifetime taken from Hannaford et al (1992).…”
Section: Resultsmentioning
confidence: 99%
“…Moity (1983) had reported transition probabilities from laboratory arc measurements in the range 255 nm to 530 nm with typical uncertainties of greater than 20%. Bergeson et al (1996) reported accurate new laboratory measurements of transition probabilities for transitions between 224 nm and 276 nm having upper levels of the 3d 6 ( 5 D)4p subconfiguration in the range 38 000 cm −1 to 46 000 cm −1 , but they did not consider levels lying higher than 46 000 cm −1 . In general, there is a serious lack of accurate experimental transition probabilities for Fe II for transitions covering the UV to VUV (below 200 nm) spectral regions or from high lying energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the uncertainty on the absolute metallicities is of the order of 30% but it is much smaller on the abundance ratios. Morton (1991); (b) Wiese et al (1996); (c) Welty et al (1999); (d) Bergeson & Lawler (1993b); (e) Biémont et al (1994); (f) Wiese et al (2001); (g) Bergeson & Lawler (1993a); (h) Bergeson et al (1994); (i) Bergeson et al (1996); (j) Fedchak et al (2000). .…”
Section: Metal Contentmentioning
confidence: 99%